Manhaj Imam al-Nawawī dalam Penyusunan Kitab al-Irsyād wa al-Taqrīb - Andi Muhammad Ihsan Yusuf (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This research aims to determine the manhaj (method) used by Imam al-Nawawī in writing the books of al-Irsyād and al-Taqrīb. This type of research is library research (library review), using qualitative descriptive analytical methods. The results of this research show that the discussion content in the book of al-Irsyād is greater than in the book of al-Taqrīb. This is because in compiling the book of al-Irsyād, Imam al-Nawawī mentioned many core and non-core things (if deemed necessary), kept Ibn al-Ṣalāh's expression and arrangement, mentioned the arguments, examples and provide additions, taḥqīq and tadqīq. As for the book of al-Taqrīb, al-Nawawī is not bound by the use of Ibn al-Ṣalāh's expressions and structures, summarizing additional meanings from the book al-Irsyād, or even not mentioning them again. Furthermore, it was found that in writing these two books, al-Nawawī did the following things: Taqyīd Mutlaq, Taṣḥīḥ Miṡāl, Tauḍīḥ Qā'idah, Syarḥ al-Ma'nā, Ziyādah Far', Rad' 'alā al-Muṣannif and Qaṣr al -'Ibārāt au al-Īṭāl on the Muqaddimah of Ibn al-Ṣalāḥ.